Doctoral Study Programs in Social Work at HBCUs: Origin and Program Development. (2nd January 2016) - Aubrey, Hal; Jordan, Tina; Stevenson, Andre P.; Boss-Victoria, Rena; Haynes, James; Estreet, Anthony; Smith, Jahmaine; Cameron, Elijah; Williams, Quotasze
ABSTRACT: Fisk University began the genesis of HBCU graduate programs in 1880. During the next fifty years, several other HBCUs established graduate programs. That group included Lincoln, Howard, and Morgan State. However, only Lincoln University established a PhD program. The primary goal of this paper is to provide a historical perspective regarding the development of social work doctoral degree programs in the context of HBCU graduate degree program development. Although HBCU social work doctoral programs have only existed since 1978, they are significant and growing academic enterprises which are expanding the pool of doctoral level social work experts and professors of color. Further, these programs should be viewed contextually as producers of scholars on the larger landscape of the academy.